2018
DOI: 10.18251/ijme.v20i3.1627
|View full text |Cite
|
Sign up to set email alerts
|

In their Own Voices: Experiences of Dalit Students in Higher Education Institutions

Abstract: This qualitative study explores the experiences of Dalit students in one of the state universities of Uttar Pradesh in India. An Interpretative Phenomenological Analysis (IPA) was conducted to understand the experiences of Dalit students at higher education institutions, including caste-based prejudice and discrimination on campus. A total of seven themes emerged indicating caste-based prejudice and discrimination against Dalit students in both explicit and subtle ways at various levels of the university. Cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Caste-based social identity is likely to be strengthened by caste-based social discrimination. For example, Nambeeshan [ 49 ] documented the discriminative experiences of the Dalit (SC-ST) students in relation to a) access to school including facilities and resources b) participation in different spheres of school life and c) social relations with teachers and peers in schools in the state of Rajasthan. Discrimination can lead to decreased school engagement and rate of attendance as well as increased absenteeism and school dropout [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Caste-based social identity is likely to be strengthened by caste-based social discrimination. For example, Nambeeshan [ 49 ] documented the discriminative experiences of the Dalit (SC-ST) students in relation to a) access to school including facilities and resources b) participation in different spheres of school life and c) social relations with teachers and peers in schools in the state of Rajasthan. Discrimination can lead to decreased school engagement and rate of attendance as well as increased absenteeism and school dropout [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, Nambeeshan [ 49 ] documented the discriminative experiences of the Dalit (SC-ST) students in relation to a) access to school including facilities and resources b) participation in different spheres of school life and c) social relations with teachers and peers in schools in the state of Rajasthan. Discrimination can lead to decreased school engagement and rate of attendance as well as increased absenteeism and school dropout [ 49 , 50 ]. Maurya [ 50 ] examined 13 Dalit narratives and found that Dalit students experienced exclusion and humiliation from classmates, teachers and administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of entrenched social categorization and impingement, there is caste-based discrimination in academic institutions. There are several Dalit discriminations in Indian academic higher institutions ranging from discrimination by fellow students, administrators, and teachers (Maurya, 2018).…”
Section: Philosophical Approachmentioning
confidence: 99%
“…There is no study of the extent of caste-based discrimination in HE institutions in Nepal. However, there are several Dalit discriminations in Indian academic higher institutions ranging from discrimination by fellow students, administrators, and teachers (Maurya, 2018). Maurya further elaborates that the extent of discrimination has led Dalit students to drop-out of higher education, and even to commit suicide in Indian HE institutions.…”
Section: Social Exclusion In He Institutionsmentioning
confidence: 99%